Compliance of Medications Prescribed From a Pediatric Emergency Department. Issue 6 (June 2015) - Sammons, Nicole Willis; Yin, Han
<x xml:space="preserve">Abstract</x> Objectives Studies regarding compliance of medications prescribed from emergency departments (EDs) have primarily been adult-based or based on self-reported data. Most pediatric studies have shown that patients with private insurance tend to be more compliant. This study aims to determine the rate of medication compliance from a pediatric ED, which medications are most likely to be filled, if there are differences in compliance based on insurance status and age, and if noncompliant patients are more likely to have unintended return visits to the ED. Methods In this retrospective chart review, a sample of consecutive pediatric patients discharged from the ED was obtained. Pharmacies were contacted to ensure prescriptions were filled. Medication compliance was inferred if a prescription was filled. Results The 152 patients included had a total of 229 prescriptions that were used for data analysis. The overall medication compliance rate was 72.5%. There was no statistically significant difference in medication compliance between age (P = 0.9), diagnosis (P = 0.26), insurance status (P = 0.3), or type of medication (P = 0.3). No difference was demonstrated for unintended return visits based on compliance (P = 0.79). Conclusions Over a quarter of patients prescribed medications were noncompliant. However, there was no statistically significant difference in compliance between age, diagnosis, insurance status, or type of medication. Unlike most previous studies, privately insured patients were just as unlikely to fill their medications as publicly insured patients, and cost did not appear to be a contributing factor to noncompliance. Therefore efforts to educate patients and their families should be widespread and unbiased.